CORRELATION OF STUDENTS’ ENGLISH LEARNING STYLE WITH STUDENTS’ ENGLISH LEARNING ACHIEVEMENT - Firnanda, Sari; Sada, Clarry; Sudarsono, Sudarsono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to find out the correlation between students? English learning style and students? English learning achievement. The present study focused on visual, auditory and kinesthetic as the measurement of students? learning style. While the achievement was taken from their English final score. The resaercher presentage the students? learning style to get numerical data. Next, the researcher correlated the first and second variables to find out the correlation. The subject of the present study are year 11 students of Al- Mukhlishin Senior High School Antibar in Mempawah Regency. The year 11 consists of four classes that has 41 males and 78 females? students. This study used correlational study. there are five different learning styles found in this study. They are visual, auditory, visual-auditory, visual-kinesthetic and visual-auditory-kinesthetic learning styles. All of learning style has strong correlation with students? English learning achievement. But some of the correlation are not positive nor significant.Keywords: Correlation, Students? English Learning Style, Students? Learning Achievement.